Meaning and Value in the Proverb of the Bugis Dialect of Bone - Ali Ali; Idris Idris; Gusti Ketut Alit Suputra; Ardianto Ardianto (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study examines the meaning and value of the proverbial Bugis dialect of Bone in Koninis Village, Simpang Raya District, Banggai Regency. The purpose of this study was to describe the meanings and values contained in the proverb of the Bugis dialect of bone. The type of research used is a descriptive approach using qualitative methods so that it is easy to understand the data in this study in the form of written words. The research location was conducted in Koninis Village, Banggai Regency. The source of the data used in this study is the results of interviews obtained from informants regarding the Bugis dialect of the Bone dialect. Data collection techniques in this study used interview and recording techniques. Furthermore, the data analysis techniques used in this study were data collection, data reduction, data presentation, and conclusions and verification. The results of this study found that there were 5 types of meaning from 17 data on the proverbial Bugis dialect of bone that had been analyzed, namely; 1) connotative meaning, 2) denotative meaning, 3) proverb meaning, 4) affective meaning, 5) association meaning. Furthermore, it was found that there are 3 types of values contained in the proverb of the Bugis dialect of Bone, namely; 1) values related to human problems with themselves, 2) values related to human problems with God, 3) values related to human problems with fellow humans.